2006
DOI: 10.1051/0004-6361:20065045
|View full text |Cite
|
Sign up to set email alerts
|

An S-shaped arc in the galaxy cluster RX J0054.0-2823

Abstract: Context. The center of the galaxy cluster RX J0054.0-2823 at z = 0.292 is a dynamically active region that includes an interacting system of three galaxies surrounded by a large halo of intra-cluster light. Aims. We report here the discovery of an S-shaped feature of total length 11 in the central region of this cluster and discuss its physical nature. Methods. We test the gravitational lensing assumption by doing a mass modeling of the central part of the galaxy cluster. Results. We very naturally reproduce p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In fact, the S‐shaped arc in the centre of the cluster appears to be the remnant of one or two spiral galaxies caught in the act of being triturated by the grinding machine (Paper I). Our extensive study of the cluster was in fact originally aimed at understanding the nature of the Arc, which in Faure et al () we ascribed to the gravitational lensing of a pair of background galaxies. But Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the S‐shaped arc in the centre of the cluster appears to be the remnant of one or two spiral galaxies caught in the act of being triturated by the grinding machine (Paper I). Our extensive study of the cluster was in fact originally aimed at understanding the nature of the Arc, which in Faure et al () we ascribed to the gravitational lensing of a pair of background galaxies. But Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the S-shaped arc in the center of the cluster appears to be the remnant of one or two spiral galaxies caught in the act of being triturated by the grinding machine (Paper I). Our extensive study of the cluster was in fact originally aimed at understanding the nature of the Arc, which in Faure et al (2007) we ascribed to the gravitational lensing of a pair of background galaxies. But Figure 4 shows that the spectrum of the Arc actually resembles an E+A ('post-starburst') galaxy at the redshift of the cluster, and where ∼ 50% of the stars formed in a galaxy-wide starburst 2.5-4 Gyr ago.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of an investigation of the diffuse intergalactic light in X‐ray emitting clusters at intermediate redshifts, we detected a puzzling S‐shaped arc‐like structure in the ROSAT cluster RX J0054.0−2823 that we tentatively identified as the gravitationally lensed image of a background galaxy at a redshift between z = 0.5 and 1.0 (Faure et al 2007). The cluster is characterized by having three dominant D class galaxies, two of which are interacting forming a dumbbell cD system.…”
Section: Introductionmentioning
confidence: 97%
“…In the course of an investigation of the diffuse intergalactic light in X-ray emitting clusters at intermediate redshifts (Melnick et al 1999), we detected a puzzling S-shaped arc-like structure in the ROSAT cluster RX J0054.0-2823 (Faure et al 2007), which we tentatively identified as the gravitationally lensed image of a background galaxy at a redshift between z=0.5 and z=1.0. The cluster, however, is characterized by having three dominant D or cD galaxies in the center, two of which are clearly interacting.…”
Section: Introductionmentioning
confidence: 86%